Effect of body weight on pain, sleep quality, and depression in patients with primary fibromyalgia syndrome - Tas, Nevsun P. (Elsevier, 2022)
Aim of the work: Obesity and fibromyalgia syndrome (FMS) are two diseases, which are becoming more common and have an impact on social life. This study aimed to evaluate the effect of body weight on pain, sleep quality, and depression in patients with primary FMS and to assess its impact on the functional status.Patients and methods: The study included 234 patients with primary FMS. The body mass index (BMI) was determined. The visual analog scale (VAS), Beck depression inventory (BDI), and the Pittsburgh sleep quality index (PSQI) were used for evaluating the patients. The Fibromyalgia impact questionnaire (FIQ) was assessed. The patients were divided into 3 groups: normal weight, overweight and obese.Results: The mean age of the patients was 40.3 +/- 11.01 years (19-65 years); 206 (88%) were female, and 28 (22%) were males. The mean BMI was 28.8 +/- 7.1 (17.7-49.1): 80 (34.2%) had a normal weight (24.4 +/- 1.8), 76 (32.5%) were overweight (26.4 +/- 1.6), and 78 (33.3%) were obese (37.9 +/- 5.9) (p < 0.001). The FIQ, BDI, and PSQI were significantly higher in the obese patients compared to the normal and overweight (p < 0.001). The BMI, VAS, BDI, and FIQ were comparable between females and males while only the PSQI was significantly reduced in males (p = 0.004). A significant correlation was found between BMI with the PSQI, BDI, and FIQ (r = 0.11, p = 0.009; r = 0.41, p < 0.001 and r = 0.35p < 0.001 respectively). Conclusion: Obesity in primary FMS patients was significantly related to pain, sleep disorders, and depression. The importance of movement and weight control in FMS is emphasized.(c) 2022 THE AUTHORS. Publishing services by ELSEVIER B.V. on behalf of The Egyptian Society of Rheumatic Diseases This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/ licenses/by-nc-nd/4.0/).
Keywords: Fibromyalgia syndrome; Pain; Obesity; Sleep quality; Depression